2020
DOI: 10.1055/s-0040-1701445
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence Supports New Perspectives in Homeopathy

Abstract: The contentious debate between homeopathy and orthodox medicine has been due to the fact that homeopathy is founded on a heuristic philosophy that is not justified by contemporary scientific evidence. In this context, however, two pillars of the method, that is, serial dilution and succussion, are poorly understood in orthodox pharmacology. The experimental data collected in the last 10 years, by means of electronic microscopy, electron diffraction and DNA arrays investigations, are consistent with the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Some homeopathic researchers have considered whether randomized controlled trials appropriately measure the expected primary outcomes from homeopathic treatment, signaling an interest in finding other pathways to identify effectiveness 107 . Nevertheless, homeopathy is experiencing a growing body of evidence including clinical trials and systematic reviews, suggesting research in homeopathy will continue to evolve 5,77,108‐112 . A recent series of clinical trial outcomes has shown improvement with homeopathic remedies for several conditions 69,94,110,113 .…”
Section: Discussionmentioning
confidence: 99%
“…Some homeopathic researchers have considered whether randomized controlled trials appropriately measure the expected primary outcomes from homeopathic treatment, signaling an interest in finding other pathways to identify effectiveness 107 . Nevertheless, homeopathy is experiencing a growing body of evidence including clinical trials and systematic reviews, suggesting research in homeopathy will continue to evolve 5,77,108‐112 . A recent series of clinical trial outcomes has shown improvement with homeopathic remedies for several conditions 69,94,110,113 .…”
Section: Discussionmentioning
confidence: 99%
“…This debate about plausibility and evidence [18][19][20][21][22] can only be settled by fundamental research.…”
Section: Introductionmentioning
confidence: 99%
“…Homeopathy is a traditional medicine that has been used worldwide for more than 200 years. Recent studies indicate that homeopathically-prepared medicines (HMs) contain source nanoparticles (NPs) [1][2][3][4][5][6][7], silicates [4,8], and other, less well-characterized structures [9][10][11][12][13][14][15]. In addition, a recent RCT-literature audit [16][17] once more confirmed a specific effect of homeopathic treatments.…”
Section: Introductionmentioning
confidence: 99%